Assessment of knowledge, attitude and practice of solid waste open burning in Terengganu, Malaysia - Ho Nyuk Onn @ Ariffin, Mariani; Wan Yacoob, Wan Nor Amalina (Thai Society of Higher Eduction Institutes on Environment, 2017)
With more than 40 percent of the world’s rubbish is burned, open burning is a significant source of atmospheric pollution globally and remains one of the main environmental issues and health concerns for many developing nations. Despite having stringent criminal penalties for illegal open burning, Malaysia encounters increasing trend in open burning incidents. A better understanding of the knowledge, attitudinal, and perception towards open burning would inform more effective intervention efforts towards changing this trend. A questionnaire survey to assess knowledge, attitude and practice of public was conducted in Kuala Terengganu. A total of 384 respondents from various demographic backgrounds participated in the survey. Descriptive analysis was used to analyse the respondents’ socio-demographic profiles. Pearson correlation was used to uncover the relationship between knowledge, attitude and practice among the respondents. Results showed that the respondents had good knowledge on open burning and showed positive attitude towards protecting the environment from the problem. However, they displayed lack of practice to tackle the problem in real life. The study also found a weak relationship between knowledge with attitude and practice on open burning. Policy-makers should, therefore, devise intervention programmes that can encourage higher practice rather than merely focusing on raising awareness.